Learn Find M So That 2 9 3 2 9 6 2 9 2 M 1

from a handpicked tutor in LIVE 1-to-1 classes

from a handpicked tutor in LIVE 1-to-1 classes

# Find m so that (2/9)^{3} × (2/9)^{6} = (2/9)^{2m - 1}

**Solution:**

Given, (2/9)^{3} × (2/9)^{6} = (2/9)^{2m - 1}.

We have to find the value of m.

For any non-zero __integers__ ‘a’ and ‘b’ and whole numbers m and n,

a^{m} × a^{n} = a^{m+n}

Here, a = 2/9, m = 3 and n = 6

m + n = 3 + 6 = 9

a^{m+n }= (2/9)⁹

So, (2/9)³ × (2/9)⁶ = (2/9)⁹

Now, (2/9)^{9} = (2/9)^{2m - 1}

The bases are equal.

On equating the powers,

2m - 1 = 9

2m = 9 + 1

2m = 10

m = 10/2

m = 5

Therefore, the value of m is 5.

**✦ Try This: **Find m so that (7/11)⁴ × (7/11)⁶ = (7/11)^{m-1}

**☛ Also Check: **NCERT Solutions for Class 7 Maths Chapter 13

**NCERT Exemplar Class 7 Maths Chapter 11 Problem 69**

## Find m so that (2/9)^{3} × (2/9)^{6} = (2/9)^{2m - 1}

**Summary:**

The value of m = 5, so that (2/9)^{3} × (2/9)^{6} = (2/9)^{2m - 1}

**☛ Related Questions:**

Math worksheets and

visual curriculum

visual curriculum